A leucine‐rich repeat receptor kinase gene confers quantitative susceptibility to maize southern leaf blight. Issue 3 (25th February 2023) - Chen, Chuan; Zhao, Yaqi; Tabor, Girma; Nian, Huiqin; Phillips, Joanie; Wolters, Petra; Yang, Qin; Balint‐Kurti, Peter
Summary: Southern leaf blight (SLB), caused by the necrotrophic fungal pathogen Cochliobolus heterostrophus (anamorph Bipolaris maydis ), is a major foliar disease which causes significant yield losses in maize worldwide. A major quantitative trait locus, qSLB 3.04, conferring recessive resistance to SLB was previously mapped on maize chromosome 3. Using a combination of map‐based cloning, association analysis, ethyl methanesulfonate and transposon mutagenesis, and CRISPR‐Cas9 editing, we demonstrate that a leucine‐rich repeat receptor‐like kinase gene which we have called ChSK1 ( Cochliobolus heterostrophus Susceptibility Kinase 1 ) at qSLB 3.04 causes increased susceptibility to SLB. Genes of this type have generally been associated with the defense response. We present evidence that ChSK1 may be associated with suppression of the basal immune response. These findings contribute to our understanding of plant disease susceptibility genes and the potential to use them for engineering durable disease resistance.